2002
DOI: 10.3171/jns.2002.97.5.1078
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced meningioma: a descriptive study of 253 cases

Abstract: The findings of this study agree with those of other studies indicating the demographic, clinical, and even genetic variability between RIM and non-RIM cases. The existence of two different subtypes of meningiomas may have profound implications for screening, early diagnosis, and therapy of meningiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 27 publications
8
167
1
5
Order By: Relevance
“…32,42,53,56,64,67,80 Strojan et al 78 reported female predominance of 1.33:1 in a survey of 126 cases of high-dose RIMs. In a review of the incidence of central nervous system tumors among survivors of the atomic bombs in Hiroshima and Nagasaki, Preston et al 53 found that excess relative risk for RIMs is higher in men than in women.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…32,42,53,56,64,67,80 Strojan et al 78 reported female predominance of 1.33:1 in a survey of 126 cases of high-dose RIMs. In a review of the incidence of central nervous system tumors among survivors of the atomic bombs in Hiroshima and Nagasaki, Preston et al 53 found that excess relative risk for RIMs is higher in men than in women.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The authors of several large studies conducted in Israel have documented a primarily calvarial location in patients treated for tinea capitis. 59,64,75 Ghim et al 17 found that 11 of 13 pediatric patients with high-dose RIMs had calvarial meningiomas, whereas skull base meningiomas were found in 4-19% of patients with RIM in whom there was a history of high-dose irradiation for primary brain tumors. 39,59,67,76 Epidemiological studies of patients with RIM linked to full-mouth dental x-rays have shown that skull base meningiomas are more common following this type of radiation exposure.…”
Section: Radiation-induced Meningiomamentioning
confidence: 99%
See 1 more Smart Citation
“…Em pacientes que receberam baixas doses (<10 Gy) é, em média 35,2 anos e 18,7 anos naqueles que receberam altas doses (>20 Gy) 7 . Mack e Wilson observaram um período de latência de 27 anos para doses moderadas (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 19 . Estes diferentes períodos de latência sugerem que o maior dano ao cromossomo causado por doses maiores de radiação induz à perda mais rápida do mecanismo de controle celular e à expressão fenotípica neoplásica mais precoce 7 .…”
Section: Discussionunclassified
“…First-degree relatives of patients with meningiomas have an increased risk of developing the disease, but the etiology remains largely unknown [3]. The only established environmental risk factor for meningiomas is ionizing radiation at both low and high doses [4][5][6][7]. There is a 2:1 female-to-male incidence ratio.…”
Section: Introductionmentioning
confidence: 99%